Web-Based Learning as a Strategy to Foster Higher Order Thinking Skills (HOTS) in Pre-Service Science Teachers - Yanto, Nurfitra; Arsyad, Arie Arma (ARRUS Journal of Social Sciences and Humanities, 2025)
This study aims to assess the effectiveness of the application of Web-Based Learning in improving HotS in prospective science teachers, so as to contribute to the development of the competence of prospective science teachers. This type of research is a pre-experimental research with a research design using one group Pretest-Posttest. A sample of 45 science teacher candidates Class of 2021. Research Instrument in the form of multiple choice test questions HOTS. Data collection is done by providing pretest-posttest. The results of descriptive statistical analysis showed the characteristics of test scores for HOTS questions for IPBA courses for prospective students of the Makassar State University science teacher Class of 2021 before and after the implementation of web-based learning. Based on the results of research and discussion, it can be concluded that the HOTS level of prospective teachers before the application of web-based learning has an average value of 30.40, while after the application of web-based learning has an average value of 89.22. The average N-Gain HOTS of prospective science teacher students after applying web based learning is 0.84 which is in the high category. It can be concluded that there is a significant increase in hots for prospective science teachers after the application of web based learning.